Carl Vett (1871-1956): Denmark’s Pioneer of Biodynamic Farming and Organic Agriculture - Paull, John; Tutturen, Tord; Halberg, Simon (Advances in Social Sciences Research Journal, 2025)
The Danish businessman Carl Christian Vett (1871-1956) spent much of his life on a personal spiritual quest. He visited Dr Rudolf Steiner in Switzerland, Mahatma Gandhi in India, he spent time in a Sufi Monastery in Turkey, and he organised five International Congresses of Psychical Research. This spiritual quest led him to Anthroposophy, the Goetheanum (in Dornach, Switzerland), and to Rudolf Steiner’s Biodynamic agriculture. Steiner called for a differentiated agriculture reliant on biological processes rather than chemistry, and the ‘Experimental Circle of Anthroposophical Farmers and Gardeners’ was founded (at Koberwitz in 1924 ) and tasked with testing and propagating his ideas. Carl Vett was the first Nordic to join the ‘Experimental Circle’ (in 1926). Vett advocated for Biodynamics (BD) encouraging Danish estate owners to adopt BD practices and promoting BD as a sound economic choice. He initiated scientific testing of BD at the Danish State Plant Culture Research Institute (1931-1934). He established a BD demonstration farm (Rødbjerggaard near Hornbæk in 1934). Vett published the first Danish Biodynamics pamphlet, a 30 page booklet: ‘The Biological-Dynamic Farming Methods’, in Danish in 1936, in some apparent disregard of the Non Disclosure Agreement signed by Experimental Circle members. Vett founded the Danish Biodynamic Association (in 1936), which published the newsletter ‘Notifications from the Association for the Promotion of Biological-dynamic Methods’ (from 1936, and marked ‘Confidential’). Ehrenfried Pfeiffer (1899-1961) took BD public with the publication of his book ‘Bio-Dynamic Farming and Gardening’ (in 1938). Vett promptly translated Pfeiffer’s milestone BD book into Danish (published 1939). WWII interrupted this BD momentum. Carl Vett was the original BD advocate in Denmark and laid the foundations for Biodynamic farming, and thereby for organic agriculture, in the country. BD and Organics now account for 4,500 hectares and 303,093 hectares, respectively, in Denmark.